Evaluation of an optimal image format for graphical data review on small screens - Krishna Prasad. (2008)
lmage review modes are a vital tool for the access and management of graphical data in digital devices (cameras, phones, etc), in that they provide users with a means to manually traverse and search for images from any existing database of stored information. These modes offer namely 2 types of visual formats applicable for an image review, The first format presents images one at a time in an undistracted manner, but requires extensive paging to be performed in order to locate a target image per a given search criteria. The second format minimizes paging actions by displaying a set of multiple images (also termed “thumbnails”) within a grid layout, allowing several pieces of work to be reviewed on screen at once.